ERROR ANALYSIS OF STUDENTS’ PRONUNCIATION ON ENGLISH SILENT LETTER AT IAIN PALANGKA RAYA - Efiansyah Efiansyah (JURNAL PENELITIAN PENDIDIKAN BAHASA DAN SASTRA, 2023)
This research is motivated by the problems some students face in pronouncing the word silent letter. The problem that generally occurs is difficulty pronouncing words that contain silent letters. At the same time, the Pronunciation of silent letters is essential to know and distinguish words that are almost similar or almost the same in Pronunciation so that people who listen to them can easily understand them. This pronunciation method is expected to be a solution for students to overcome difficulties pronouncing words containing silent letters. This study aimed to measure their ability to pronounce words that contain silent letters in the English Tadris study program at IAIN Palangka Raya. This study uses a quantitative research method with an experimental design. In giving treatment, the researcher included vocabulary containing silent letters to make it easier for them to understand in the future. The population in this study were students of class 2019, and only 1 class was taken at the English language education study program at IAIN Palangka Raya. Researchers used one class as a sample, and this class was an experimental class consisting of 30 students. From the tests, several people had difficulty pronouncing silent letters, influenced by their mother tongue (L1). However, their ability level is still high in understanding razor letters; only a few cannot.